Influence of rhizobacteria on nitrogen fixation, nitrogen remobilisation and plant growth promotion in maize (Zea mays L.) - Kuan, Khing Boon (2015)
Currently, there has been a renewed interest in plant growth promoting rhizobacteria (PGPR) as biofertiliser in sustainable agriculture. High yielding maize varieties are widely available to growers but their yields depend heavily on high nitrogen (N) nutrient inputs. Following that, a substantial amount of unused applied fertiliser-N would be leached and/or volatilised to the atmosphere and raise environmental concerns. Alternatively, we hypothesised that N remobilisation in plant can be manipulated using PGPR to increase the grain yield, based on an understanding that the plant N remobilisation is directly correlated to its plant senescence. Thus, a series of laboratory and glasshouse studies were conducted at Universiti Putra Malaysia (UPM) with the following objectives; (i) to isolate, characterise and identify effective indigenous PGPR,(ii) to determine the effects of PGPR inoculation on N uptake, plant growth and ear yield of maize and (iii) to determine the amount of N2 fixed by PGPR and their influence on N remobilisation in maize over time (D50 and D65). PGPR were isolated from Cash Crop Teaching and Research Field, UPM and Paddy Field Rehabilitation Project, Sik, Kedah using Tryptic Soy Agar (TSA) and streaked on N-free semisolid malate medium (Nfb) and Pikovskaya agar. Indole-3-acetic acid (IAA) production was evaluated using colorimetric test. Biochemical tests of 57 PGPR isolates showed that 10 PGPR of varied Gram stains were positive for multiple traits namely N2 fixation, phosphate solubilisation and IAA production of up to 13 μg mL-1. These PGPR were inoculated on maize seedlings under in-vitro condition and the four effective PGPR were identified using 16S rDNA gene sequencing as Klebsiella sp. Br1, Klebsiella pneumoniae Fr1, Bacillus pumilus S1r1 and Acinetobacter sp. S3r2. N2 fixation of PGPR in association with maize was determined using 15N isotope dilution technique in a glasshouse experiment with two harvests, namely prior to anthesis (D50) and ear (D65) harvests. The treatments were an uninoculated control, a reference PGPR (Bacillus subtilis UPMB10) and four indigenous PGPR (Br1, Fr1, S1r1 and S3r2). PGPR inoculation had increased bacterial populations in the non-rhizosphere (4.8×107 cfu g-1, 5.9×107 cfu g-1), rhizosphere (1.5×108 cfu g-1, 6.3×108 cfu g-1) and root-endosphere (3.0×104 cfu cm-1, 7.3×104 cfu cm-1) of maize under in-vitro and glasshouse conditions, respectively. PGPR inoculation also increased the chlorophyll content (20.2%, 11.5%), total N uptake (58.6%, 69.6%),plant height (31.0%, 20.3%), dry weight of top (51.3%, 33.8%) and root (56.0%, 43.5%) of maize under these two conditions. Ear yield of PGPR inoculated maize increased up to 30.9% under glasshouse condition. The results of 15N isotope dilution study showed PGPR inoculation namely by Bacillus pumilus S1r1 had the highest N2 fixing capacity of 30.5% Ndfa (N derived from atmosphere) (262 mg N2 fixed plant-1) and 25.5% Ndfa (304 mg N2 fixed plant-1) of the total N requirement of maize top, which was equivalent to 14.0 kg N ha-1 and 16.2 kg N ha-1 at D50 and D65, from an extrapolated 53333 plants ha-1, respectively. The older plants contributed more N2 fixed per plant although the rate of N2 fixation has peaked prior to anthesis, due to continuous N2 fixation throughout plant maturity. Leaves (old, ear and young), tassel and stalk served successively as N sinks and sources towards ear formation. N remobilisation and plant senescence in maize was delayed by PGPR inoculation, as suggested by the significant interactions (p<0.05) found between PGPR and time of harvests in N uptake and at. % 15Ne parameters of tassel, respectively. Moreover, the phenomenon was also supported by the significantly lower (p<0.05) N uptake in the inoculated tassels of maize treated with PGPR namely B.pumilus S1r1, K. pneumoniae Fr1, B. subtilis UPMB10 and Acinetobacter sp. S1r1 at D65 harvest. This study provided evidence that Bacillus pumilus S1r1 inoculation can biologically fix atmospheric N2 and provides an alternative way besides plant breeding to manipulate N remobilisation in maize plant for higher ear yield at reduced fertiliser- N rate.